RESTORATIVE JUSTICE FOR CONVICTIONS WITH MARIJUANA NARCOTICS: RESTORATIVE JUSTICE BAGI TERPIDANA NARKOTIKA JENIS GANJA - Hidayat, Riyan (UPMI Proceeding Series, 2023)
Restorative justice is an alternative settlement of criminal cases in which the mechanism of criminal justice procedures focuses on punishment which is converted into a dialogue and mediation process involving perpetrators, victims, families and other related parties to jointly create an agreement on the settlement of criminal cases fair and balanced for victims and perpetrators by prioritizing restoration to its original state, and restoring good relations in society. The Supreme Court considers that it is necessary to apply Restorative Justice for several cases, one of which is the narcotics case which must be carried out by all district court judges and heads of high courts through the Decree of the Director General of the General Judiciary Agency of the Supreme Court of the Republic of Indonesia Number 1691/DJU/SK/PS.00 /12/2020 concerning the Enforcement of Guidelines for the Implementation of Restorative Justice in the General Courts (abbreviated as "Decisions") on December 22, 2020. A person is named a suspect on the basis of preliminary evidence obtained from an investigation conducted by the Police. then a suspect should be suspected of being the perpetrator of a crime, in the development of the legal process for abuse a termination was carried out at the investigation stage by the police on the grounds that in cases of criminal acts of narcotics abuse referring to Republic of Indonesia National Police Regulation Number 8 of 2021 concerning Handling of Crimes Based on Restorative Justice.